(untitled) (Academicia Globe: Inderscience Research, 2021)
Language is the chief means by which the human personality exercises itself and fulfills its basic need for social interaction with other persons. Robert Lado wrote that language functions owing to the language skills. A person who knows a language perfectly uses a thousand and one grammar lexical, phonetic rules when he is speaking. Language skills help us to choose different words and models in our speech.Before generating ideas, it is important to understand more about problems. It is not essential, but the material that follows could provide better insight into the types of situations in which idea generation activities are applied. You also might want to use it for general problem-solving training or as background information for training in idea generation activities.